Comparative evaluation of effectiveness of 2% lignocaine hydrochloride with clonidine hydrochloride versus 2% lignocaine hydrochloride with adrenaline bitartrate as local anesthetic for adult patients undergoing surgical extraction of impacted mandibular third molars: A randomized controlled clinical study - Shreyas H Gupte; Rinku D Kalra; Thomson M Dcruz; Sahil Kamble; Ranjana S Patnaik (Wolters Kluwer Medknow Publications, 2021)
Background and Objectives: Clonidine is a common additive to local anesthetics for various regional and local nerve blocks. However, its effectiveness in dentistry has not yet been fully explored. Thus, this study was performed to evaluate the quality of anesthesia, vasoconstrictive effects, hemodynamic response, and pain control using a solution of 2% lignocaine hydrochloride with clonidine hydrochloride in comparison with the standard solution of 2% lignocaine hydrochloride and adrenaline bitartrate for pterygomandibular nerve blocks. Materials and Methods: A parallel arm, triple-blind randomized controlled study was conducted on 152 patients belonging to ASA-I (American Society of Anesthesiologists) category in the age group of 18-45 years, requiring surgical extraction of impacted mandibular third molars. The patients were divided equally into two groups randomly by computer-generated sequence; Group 1: 2% lignocaine hydrochloride with 1 ml of clonidine hydrochloride (150 μg/ml) and Group 2: 2% lignocaine hydrochloride with adrenaline bitartrate 1: 80,000 (12.5 μg/ml). The variables evaluated were systolic, diastolic, and mean arterial blood pressures, heart rate (HR), blood loss, onset, depth (pain), and duration of anesthesia. Results: There was a statistically nonsignificant difference seen between the two groups (P > 0.05) for the onset of anesthesia, pain assessed, and blood loss, whereas a statistically highly significant difference was seen for cardiovascular variables (systolic, diastolic and mean arterial blood pressures, and HR) at various intervals with higher values for Group 2 (P < 0.001) and for the duration of action of local anesthesia (LA), with higher values for Group 1 (P < 0.001). Conclusions: Clonidine as an additive to lignocaine has proved to have the onset of action, vasoconstrictive properties, and pain control, equivalent to adrenaline. However, with better stability of hemodynamic variables and prolonged duration of action of LA with clonidine, it can be considered as a better, safer, and more effective additive to lignocaine than adrenaline